Pendampingan Praktek Ibadah Sholat Dhuha di SD IT Bakti 2 Nairatul Jannah Kota Padang - Pohan, Abdul Hakim; Kustati, Martin; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2023)
Students are guided to perform Duha prayers in accordance with Islamic law. In this way, students do not make mistakes in pe5rforming the Duha prayer and can perform the Duha prayer well and correctly in accordance with the guidance in Islam. The aim in this case of accompanying the Dhuha prayer is to familiarize yourself with performing the Sunnah Dhuha prayer. By getting used to Sunnah Dhuha prayers, you can improve your attitude of discipline, responsibility and independence. Meanwhile, the method for implementing this service uses the PAR method which is carried out in stages. What is expected from mentoring through the practice of sunnah prayers in addition to obligatory worship. By getting used to performing Duha prayers according to the predetermined time, students can get used to performing Duha prayers at the time determined by the school in accordance with Islamic teachings, besides that it will also make students more disciplined both in carrying out Duha prayers and in other activities. Furthermore, students are accustomed to queuing in an orderly manner when taking ablution water. By getting used to queuing students can be more orderly and regular in taking ablution water and in other activities. By queuing students are also taught about patience when waiting for their turn to take ablution water.